Anthropometrics, body composition, physical activity, physical fitness and body image perception among female adolescents in Sarikei, Sarawak / Patricia Pawa Pitil - Pawa Pitil, Patricia (2013)
This study examined the body image perception and its relationships to anthropometry, body composition, physical activity and fitness among 439 female adolescents in Sarikei, Sarawak. A set of questionnaires were used to gather information on demographic factors, physical activity (GPAQ) and body image perception (MBIS). Anthropometry, body composition and physical fitness were also determined. There were significant differences (p<.05) in physical activity levels observed in relation to MBIS factors among the three groups (veiy active, moderately active and inactive groups). The inactive participants were more dissatisfied with body image. There were no significant correlations between body image satisfaction and skinfold body fat percentage in very active participants, or with weight in moderately active participants, and with waist in inactive participants (p>.05). All other correlations were significant (p<.05). Significant negative correlations were observed between waist to hip ratio and body image satisfaction in both very active (p<.05) and moderately active (p<.05) participants. The total body strength and flexibility were significantly correlated with body image satisfaction in all groups (p<.05). However, only aerobic fitness was significantly correlated with body image satisfaction in inactive participants (p<.05). There was no significant correlation observed between muscular endurance and body image satisfaction in all studied groups. The inactive group was observed to have more body image issues when compared to the other counterparts. Therefore, the present study recommends that intervention and prevention programs on physical activity and fitness would be beneficial in reducing body dissatisfaction among adolescents.